Kontroversi dan Penerimaan Pemikiran Amina Wadud dalam Dunia Islam: Kajian Sosiologis dan Historis dalam Perspektif Peradaban Islam Kontemporer - Handayani, Ani; Aidil, Aidil; Fauzi Nazar, Reza; Nurhayati, Ria; Ahsanul Aziz, Muhammad (Zawiyah: Jurnal Pemikiran Islam, 2026)
The issue of women’s leadership in Islam remains a subject of theological and social debate among contemporary Muslim societies. One of the figures who has triggered a global discourse on this issue is Amina Wadud, particularly following her act of leading a Friday prayer in 2005. This study aims to analyze Amina Wadud’s thought on gender equality and women’s leadership in religious worship, as well as to examine the responses of the Muslim world to these ideas from a sociological and historical perspective of contemporary Islamic civilization. This research employs a qualitative approach in the form of library research, utilizing the works of Amina Wadud as primary sources and various scholarly articles and academic journals as secondary sources. The analysis is conducted using a feminist hermeneutical approach to understand the construction of gender-just interpretations of the Qur’an. The findings indicate that Amina Wadud’s interpretation emphasizes the principle of gender equality in Islam and argues that there is no explicit textual prohibition in the Qur’an against women’s leadership in certain contexts. Muslim responses to this line of thought vary, ranging from normative rejection to progressive acceptance, influenced by cultural, historical, and social factors. This study underscores the importance of inclusive dialogue among academics, religious scholars, and Muslim communities in responding to feminist interpretations of Islam. Keywords: Amina Wadud, gender equality, women’s leadership, contemporary Islam, feminist hermeneutics.